2015
DOI: 10.1051/fruits/2015034
|View full text |Cite
|
Sign up to set email alerts
|

Preference ofZeugodacus cucurbitae(Coquillett) for three commercial fruit vegetable hosts in natural and semi natural conditions

Abstract: Introduction. Host preference of Zeugodacus cucurbitae in three vegetables was determined under choice and no-choice experiments. Materials and methods. The experiments were conducted in both semi-natural (under cage) and natural (no cage) field conditions. The trials were run for three seasons between March 2013 and July 2014 in Morogoro Region, Tanzania. In each season, two sets of plots of watermelon Citrullus lanatus, cucumber Cucumis sativus and pumpkin Cucurbita sp., were established in mono and mixed cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In Africa, member of the genus Dacus (native to Africa) have been the most dominant and damaging fruit flies resulting in significant yield losses [11]. However, the problem was further compounded by the widespread invasion of the alien invasive species Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) (formerly known as Bactrocera cucurbitae ), very often leading to total crop failure [12,13] due to the pest’s is high fecundity [13] and the lack of natural enemies on the continent. Moreover, Z. cucurbitae is highly polyphagous posing a serious threat for production of non-cucurbitaeous crops [14].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, member of the genus Dacus (native to Africa) have been the most dominant and damaging fruit flies resulting in significant yield losses [11]. However, the problem was further compounded by the widespread invasion of the alien invasive species Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) (formerly known as Bactrocera cucurbitae ), very often leading to total crop failure [12,13] due to the pest’s is high fecundity [13] and the lack of natural enemies on the continent. Moreover, Z. cucurbitae is highly polyphagous posing a serious threat for production of non-cucurbitaeous crops [14].…”
Section: Introductionmentioning
confidence: 99%
“…Young fruits of watermelon were highly infested during monitoring. The cucurbit fruit fly favored early stages of fruits, and the infested fruits failed to develop properly and dropped-off from the plant . Earlier studies on fruit flies have also reported that the adult females preferred unopened flowers and young fruits for egg laying. ,, Infestation rate recorded after fruits harvesting and incubation showed variation among treatments and seasons.…”
Section: Discussionmentioning
confidence: 92%
“…Zeugodacus cucurbitae prefers watermelon, pumpkin and cucumber and can cause up to 100% loss in an unprotected crop . On cucurbit plants, an average yield loss of 53% due to damage by native species was recorded on pumpkin ( Cucurbita pepo L.) and tomatoes ( Solanum lycopersicum L. ). , Depending on the environmental conditions, susceptibility of the crop species, and the geographic location, the extent of losses varies between 30 to 100%. …”
Section: Introductionmentioning
confidence: 99%
“…Studies of oviposition preference have been conducted on Z . cucurbitae (Sarwar et al., ; Mwatawala et al., ), but rigorous tests of the preference–performance hypothesis are not yet available for this species — but see Akol et al. (), Joachim‐Bravo & Zucoloto (), Joachim‐Bravo et al.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, whereas various insect studies (reviewed in Gripenberg et al, 2010) support the preference-performance hypothesisi.e., oviposition preferences have evolved to maximize offspring growth and survival; also known as the 'mother knows best' principle; Valladares & Lawton, 1991)other studies do not (e.g., Marchioro & Foerster, 2014;Hufnagel et al, 2017). Studies of oviposition preference have been conducted on Z. cucurbitae (Sarwar et al, 2013;Mwatawala et al, 2015), but rigorous tests of the preference-performance hypothesis are not yet available for this speciesbut see Akol et al (2013), Joachim-Bravo & Zucoloto (1997, Joachim-Bravo et al (2001), and Muthuthantri & Clarke (2012) for data on other tephritid species. In short, the present study demonstrates a host plant-mediated effect on a crucial parameter of adult fitness (male mating success) in the laboratory but similarly demonstrating this pattern in the field will be difficult, given the many ecological factors that may influence this relationship.…”
Section: Discussionmentioning
confidence: 99%